1988
DOI: 10.1002/1097-0142(19881215)62:12<2501::aid-cncr2820621209>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Six-year results of a multimodality treatment strategy for locally advanced breast cancer

Abstract: Between 1976 and 1982, 59 patients with locally advanced breast cancer were treated with preoperative supervoltage radiotherapy, adjuvant preoperative and postoperative hormonochemotherapy, and modified radical mastectomy. Systemic treatment, which was started simultaneously with radiotherapy, consisted of a combination of daily oral tamoxifen and a monthly alternation of Doxorubicin + vincristine and cyclophosphamide + methotrexate + 5-fluorouracil (CMF). One of each cycle was given preoperatively at half dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
3

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 15 publications
0
22
0
3
Order By: Relevance
“…Median disease free interval was 46 months and estimated median survival more than 6 years; toxicity from treatment was high. Piccart et al (1988) treated 59 patients with locally advanced breast cancer by combined radiotherapy, tamoxifen and chemotherapy (doxorubicin and vincristine alternating with CMF). All patients became operable and had total mastectomy and axillary clearance after which chemotherapy was resumed for 1 year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Median disease free interval was 46 months and estimated median survival more than 6 years; toxicity from treatment was high. Piccart et al (1988) treated 59 patients with locally advanced breast cancer by combined radiotherapy, tamoxifen and chemotherapy (doxorubicin and vincristine alternating with CMF). All patients became operable and had total mastectomy and axillary clearance after which chemotherapy was resumed for 1 year.…”
mentioning
confidence: 99%
“…Only when very large differences are seen against historical controls can we have some certainty that progress has been made; this is not yet the case with the studies of primary chemotherapy reported so far. Undoubtedly, primary chemotherapy achieves a high clinical response rate in locally advanced breast cancer, but residual disease is found in the majority of mastectomy specimens (Israel et al, 1986;Piccart et al, 1988). Nevertheless, despite this inability of chemotherapy reliably to induce pathological complete remission, it does facilitate implementation of radical local treatment.…”
mentioning
confidence: 99%
“…The median number of metastatic lymph nodes for patients who received adjuvant chemotherapy after surgery was 11 (range 0-35) and five (range 1-18) for those treated with neoadjuvant chemotherapy prior to surgery. The median time between diagnosis and HDC/ASCI for the entire group was 7 months (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] At 5 years, the best reported relapsefree survival for patients with four to nine metastatic lymph nodes is 46-67%; 1 at 10 years, 32-47%. 2 Moreover, the risk of relapse increases with each additional metastatic lymph node found at surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation